INTERNALIZATION OF MULTICULTURAL VALUES IN LEARNING ISLAMIC EDUCATION AT MTs YASTI BENGKAYANG - Ubabuddin Ubabuddin; Triyo Supriyatno; Nuraini Nuraini; Susilawati Susilawati; Suhari Suhari (Conciencia, 2020)
This research was conducted at MTs Yasti Bengkayang. As an educational institution located in the transmigration area and bordered by the State of Malaysia, it has definitely the uniqueness and diversity that has been bought by everyone from their original area, then fused into a multicultural society with the ego and interests of each individual. As an Islamic educational institution in a multicultural society, MTs Yasti Bengkayang always strives to make Islam as a religion of rahmatan lil alamin through the internalization of multicultural values in schools. The purpose of this study was to find out, identify, and uncover multicultural values contained in Islamic religious education learning and instilling methods that have been carried out at MTs Yasti Bengkayang. This method was used qualitative with a case study approach. The results showed that: 1) multicultural values contained in the learning of Islamic religious education at MTs Yasti Bengkayang such as; inclusive values, peace, justice, solidarity, affection, mutual help, and forgiveness; 2) the method of investing in multicultural values were teaching, example, guidance, and habituation.